Physicochemical Profile of Yucca filamentosa and a Comparative Chemical Profiling Study of its Mother Tinctures Prepared in and Outside India - Biswas, Bibaswan; Maity, Satyajit; Majumdar, Paulami; Choubey, Gurudev; Soren, Arti (Homœopathic Links, 2025)
Yucca filamentosa is primarily used in homeopathy for treating gastric ailments, supported by its saponin content. Despite being exotic to India with limited availability, its mother tincture is widely accessible in the country. Given these factors, assessing the quality of these medicines in India is crucial. Therefore, alongside pharmacopeial standardization, a comparative chemical profiling study was conducted on mother tinctures sourced from plants grown in India (OM), those produced in India (IM), and those manufactured abroad (AM).The pharmacopeial parameters of the raw drug, such as loss on drying, different ash values, extractive values in various solvents, and volatile oil content, were measured. Additionally, phytochemical screening of the raw drug in different extractive solvents was performed. Subsequently, the physicochemical parameters including organoleptic characteristics, sediments, total solids, and ultraviolet–visible absorption spectra of OM, IM, and AM were compared. Further comparative phytochemical screening and qualitative high-performance thin-layer chromatography (HPTLC) analysis were conducted.The pharmacopeial data for the raw drug were reported for the first time. The comparative study on the mother tinctures OM, IM, and AM revealed significant chemical differences.The comparison of the three mother tinctures (OM, IM, and AM) highlighted substantial chemical variations, underscoring the need for more rigorous chemical and biological evaluations.
Keywords: drug standardization; homeopathy; physicochemical; Yucca filamentosa